1998
DOI: 10.1108/09544789810197855
|View full text |Cite
|
Sign up to set email alerts
|

The use of quality tools and techniques in product introduction: an assessment methodology

Abstract: Based on fieldwork carried out on two Engineering and Physical Sciences Research Council‐funded projects in the area of design, the paper presents the details of an assessment approach which has been developed to assess the use and application of quality tools and techniques in the new product design and development process. Its use will help management recognise the symptoms, root causes, issues and problems that are adversely affecting NPDD, with respect to application (or lack of it) of quality tools and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 3 publications
0
47
0
3
Order By: Relevance
“…Despite the proven benefits of these tools and techniques in NPD, they are relatively under-utilized in the development of new products (Mahajan and Wind 1992;Lamb and Dale 1994;Nijssen and Lieshout 1995), especially as compared with their widespread application in established manufacturing processes (Spring et al 1998). Thia et al (2005) have suggested several possible reasons for this phenomenon, including: (i) the lack of involvement of market-research companies to assist in solving NPD-related problems; (ii) a low level of awareness among project managers; and (iii) the management's lack of faith in the effectiveness of the tools for NPD.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the proven benefits of these tools and techniques in NPD, they are relatively under-utilized in the development of new products (Mahajan and Wind 1992;Lamb and Dale 1994;Nijssen and Lieshout 1995), especially as compared with their widespread application in established manufacturing processes (Spring et al 1998). Thia et al (2005) have suggested several possible reasons for this phenomenon, including: (i) the lack of involvement of market-research companies to assist in solving NPD-related problems; (ii) a low level of awareness among project managers; and (iii) the management's lack of faith in the effectiveness of the tools for NPD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Vinodh, Kumar, and Vimal (2014) showed how the implementation of lean six sigma can reduce production defects and lead to financial gains and customer loyalty while Ooi et al (2013) found that the implementation of TQM had a positive impact on employee's quality of work life. Business improvement initiatives are central to process improvement and by extension, can enhance organisational performance and competitiveness (Glaser 1993, Spring et al 1998, Gupta, McDaniel, and Herath 2005. While it can be argued that improvement initiatives, in general, serve a common purpose of organisational enhancement, the initiatives themselves come in various forms and serve various specific purposes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The adoption of one design tool leads to the motivation or recommendation to use others (Spring et al 1998) A9.…”
Section: A5mentioning
confidence: 99%